A comparison of consumer's choice to brand packaged foods in India: an empirical investigation. (1st January 2013) - Malhotra, Gunjan; Ranjan, Jayanthi
Brand packaged food have become famous in the Indian markets and retail general stores supply these products with sealed aluminium laminates. Ready-to-eat (RTE) snacks and food has reached a US 5 billion market in year 2009. RTE foods do not require any cooking and can be consumed by just putting the packet in the boiling water or in the microwave for few seconds. That is 'just heat and eat'. With the expansion of the retail markets in India the demand and popularity of RTE foods are on the rise. Through our study we wanted to determine the factors that affect the purchase decision of Indian consumers of RTE foods. We also wanted to understand the consumption patterns of the respondents in terms of taste, convenience and availability. The research is based on target of youth in the age of 20−30 years either working or studying in various colleges across India and studied their consumption pattern of RTE foods. We studied five major players in this market MTR, Aashirvaad, Kitchens of India, Haldiram's and Amul.